Resiliensi Sebagai Gambaran Adaptasi Psikologis Remaja Penyintas Banjir dan Tanah Longsor di Aceh Tamiang - Sumarti Endah Purnamaningsih; Iswanti Purwaningsih; Dhiya Urrahman; Agus Setiyawan (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
Background: Indonesia is a disaster-prone country, where floods and landslides frequently cause not only physical damage but also psychological impacts, particularly among children and adolescents. Adolescents represent a vulnerable population due to their developmental stage, emotional regulation process, and ongoing adaptation to environmental changes. Resilience is an important psychological capacity that enables adolescents to adapt positively, cope with adversity, and maintain mental well-being after experiencing traumatic events such as disasters. Objective: To describe the level of resilience as a psychological adaptation among adolescents affected by flood and landslide disasters in Aceh Tamiang Regency. Methods: This study employed a quantitative descriptive design with a cross-sectional approach. A total of 616 junior high school students were recruited using a census study approach. Resilience was measured using the Child and Youth Resilience Measure-Revised (CYRM-R) consisting of 17 items with two dimensions: personal resilience (10 items) and caregiver resilience (7 items). Results: Most respondents experienced direct impacts from the disaster, including evacuation (81.49%), moderate to severe housing damage (65.74%), and loss of animals or valuable belongings (62.01%). Overall, most adolescents demonstrated a high level of resilience (81.01%), while 17.86% had moderate resilience and 1.14% had low resilience. Based on the dimensions, high personal resilience was identified among 77.27% of respondents, while caregiver resilience showed a higher proportion, with 83.28% categorized as high. Conclusion: The majority of adolescents affected by flood and landslide disasters demonstrated high resilience, indicating positive psychological adaptation despite experiencing stressful disaster-related events. Caregiver support appeared to be an important component in strengthening adolescent resilience during the post-disaster recovery process. Implication: These findings highlight the importance of integrating resilience-based interventions into psychiatric nursing services, particularly through family involvement and school-based psychosocial programs, to strengthen adolescent coping abilities and support mental health recovery following disasters.